2020
DOI: 10.1080/22221751.2020.1760144
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of infectious SARS-CoV-2 from urine of a COVID-19 patient

Abstract: SARS-CoV-2 caused a major outbreak of severe pneumonia (COVID-19) in humans. Viral RNA was detected in multiple organs in COVID-19 patients. However, infectious SARS-CoV-2 was only isolated from respiratory specimens. Here, infectious SARS-CoV-2 was successfully isolated from urine of a COVID-19 patient. The virus isolated could infect new susceptible cells and was recognized by its' own patient sera. Appropriate precautions should be taken to avoid transmission from urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
303
0
19

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(326 citation statements)
references
References 12 publications
4
303
0
19
Order By: Relevance
“…This outcome may depend on the inclusion/exclusion search criteria of our review. Other reviews have focused on gastrointestinal symptoms and reported a higher prevalence in more severe patients ( 46 , 65 ). Our findings suggest the importance of screening the viral positivity of patients' stool even after negative results of their respiratory tract swabs.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome may depend on the inclusion/exclusion search criteria of our review. Other reviews have focused on gastrointestinal symptoms and reported a higher prevalence in more severe patients ( 46 , 65 ). Our findings suggest the importance of screening the viral positivity of patients' stool even after negative results of their respiratory tract swabs.…”
Section: Discussionmentioning
confidence: 99%
“…2 ) [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] . More importantly, the infectious virus has also been detected in feces and urine of patients [45] , [46] , [47] , which triggered the public’s high concern about fecal-oral transmission and/or wastewater transmission. The virus that has been found can remain stable for up to a few days at 20 °C in wastewater [48] .…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the available evidence demonstrated that the occurrence of SARS-CoV-2 infection in human intestinal organoids might recapitulate enteric infection of COVID-19 patients, and the human intestinal tract might represent an additional route of SARS-CoV-2 transmission ( Zhou et al, 2020a ). In the meantime, SARS-CoV-2 RNA was also detected in the urine sample ( Sun et al, 2020 ), sink, and toilet ( Ong et al, 2020 ) of COVID-19 patients, and the positive urine duration was more than one month ( Sun et al, 2020 ). Notably, Sun et al (2020) successfully isolated infectious SARS-CoV-2 from the urine of a COVID-19 patient, suggesting that SARS-CoV-2 might be secreted through the human urinary system.…”
Section: Introductionmentioning
confidence: 99%